Unlocking HR’s Hidden Treasure on Innovation Capability: The Mediating Role of Knowledge Management Capacity - Mohd Yusof, Ahmad Nizam; Ahmad, Mohamad Fahimi (Information Management and Business Review, 2024)
Effective innovation is possible when one can innovate. Malaysia has serious problems due to a lack of R&D and innovation skills. Furthermore, small and medium-sized firms (SMEs) in developing nations have received less attention in past research on Malaysian innovation. A quantitative strategy is employed to meet the study’s goals. A survey approach is used to collect data from the owners, chief executives, and management of ICT SMEs. The research collected and analyzed a total of 200 respondents. The research models and hypotheses were assessed using the Partial Least Squares (PLS) technique. This research comprises the difference between Innovative Centric Human Resource Management (ICHRM) (Acquisition; Development; Egalitarian; Collaborative; Documentation, Information System) and Innovation Capability (Radical; Incremental), also the relationship between ICHRM and Innovation Capability, using Knowledge Management Capacity as a mediator. Based on the findings of this study, the majority of HRM practices are suitable for SMEs’ incremental innovation capabilities. This study also presents empirical evidence of the impact of ICHRM on knowledge management capacity on innovation, focusing on the impact of each dimension in ICHRM components that were linked to organizational processes, with a focus on the influence on incremental and radical innovation.